Maintaining Three Languages The Teenage Years - Wang, Xiao-lei (Parents' and Teachers' Guides, 2015)
The teenage years are a fascinating time in the life of any family, but what happens when the challenges of parenting teenagers are combined with the desire to help your children build on their multilingual abilities? In this follow-up to Growing up with Three Languages: Birth to Eleven, Xiao-lei Wang offers a unique insight into the dynamics of a multilingual family. She combines practical, evidence-based advice with rich detail from observations of her own family to offer support and inspiration on an aspect of multilingual parenting that has received comparatively little attention. By placing language within the wider context of teenagers’ cognitive and social development, this book will enable parents everywhere to help and guide their children through the next step in their multilingual journey